THERMOELECTRIC STUDIES OF p-TYPE Mg3Sb2 BASED MATERIALS - Pao, Yat Hang (My University, 2025)
This M.Sc thesis investigates p-type α-Mg3Sb2 based thermoelectric materials. High- performance Mg3Sb2 based materials are typically doped with expensive and scarce elements such as Te, Nd, Gd, Ho, Yb, Eu… etc. In this study, cheap and abundant dopants such as Zn, Na, Cd, Bi, Pb etc. were attempted. Zn & Na co-doping as well as Zn & Ag co-doping has shown promising thermoelectric properties. Cd doped Mg3Sb2 materials have shown thermal instability at high temperatures which led to thermal decomposition. The co-doping of Zn & Bi, Pb and K has failed. Pure phase Mg3Sb2 is inherently a p-type material. However, the n-type materials achieve much higher thermoelectric figure of merit zT value than their p-type counterparts. The best performing n-type Mg3.15Mn0.05Sb1.5Bi0.49Te0.01 possesses an average ZT ~1.25 (from 300 K to 723 K) and a peak ZT 1.85 at 723 K (Chen et al., 2018), whereas p-type YbCd1.85Mn0.15Sb2 has the highest figure of merit ZT of 1.14 at 650 K (Guo et al., 2011).
Keywords: Thermoelectric; Figure of Merit; Solid State Chemistry; Magnesium Antimonide; Mg3Sb2; Inorganic